(untitled) (Biological Sciences - PJSIR, 2003)
The world of nature abounds in organic compounds of every conceivable structural classes. Everv vcar Organic Chemists isolate and characterize a lot of compound from medicinal plants all over the World. The isolation and characterization of 2 ’, 4 ’-dihvdroxy-6’-metho"’Y-3, 4-methylenedioxy dihydrochalcone reported in 1990 from the bark of Iryanthera sagotiana (Benth.) Warb. In 1997 the isolation and characterization of 2’, 4’, 6’-trihydroxy-4-methoxydihydrochalcone from the woody part and the ripe fruit of lryanthera Laevis reported. The syntheses of these two dihydrochalcones have not been reported yet. In this paper we wish to report the syntheses of the above t:vvo dihydrochalcones by Claisen - Schmidt reaction and other subsequent steps